Combine effects of square root functional response and prey refuge on predator–prey dynamics. (2nd November 2021) - Panja, Prabir
ABSTRACT: In this paper, a predator–prey interaction mathematical model has been developed incorporating prey refuge and square root functional response. It is considered that the prey species grow logistically in the absence of predator. Then, positivity and boundedness of solutions of our proposed system have been investigated. After that all possible equilibrium points of our proposed system are determined. Also, the local stability of our proposed system around the equilibrium points has been discussed. Global stability of interior equilibrium is also investigated. The Hopf bifurcation analysis has been done with respect to prey refuge rate (c), conservation rate of prey (b) and death rate of predator (d). Finally, some numerical-simulated results have been presented to test the validity of our theoretical findings.